2020
DOI: 10.2196/17269
|View full text |Cite
|
Sign up to set email alerts
|

Providing Unique Support for Health Study Among Young Black and Latinx Men Who Have Sex With Men and Young Black and Latinx Transgender Women Living in 3 Urban Cities in the United States: Protocol for a Coach-Based Mobile-Enhanced Randomized Control Trial

Abstract: Background The US National HIV/AIDS Strategy 2020 calls for increasing access to care, improving outcomes of people living with HIV, and targeting biomedical prevention efforts, including access to pre-exposure prophylaxis (PrEP) in communities where HIV is most heavily concentrated. The cities of Baltimore, Maryland (MD); Washington, DC; and Philadelphia, Pennsylvania (PA) are disproportionately burdened by high rates of new cases of HIV infection, with high prevalence among young Black and Latinx… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 86 publications
0
10
0
Order By: Relevance
“…Outside of HIV research, several large cohorts, such as the NIH's Precision Medicine Initiative Cohort [24] and the Black Women's Health Study [25], recruit and follow up to 1 million participants across the United States using predominantly technology-based methods. Technology is increasingly integrated into HIV research through sampling and recruitment methods via online advertisements on social media and dating apps as well as electronic peer referral methods [26,27]; electronic and remote data collection [28][29][30]; and remote specimen collection for biologic measures [31][32][33]. These tools have permitted enrollment of large samples of participants for behavioral surveys [34][35][36], cohort research [37][38][39], and intervention research [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…Outside of HIV research, several large cohorts, such as the NIH's Precision Medicine Initiative Cohort [24] and the Black Women's Health Study [25], recruit and follow up to 1 million participants across the United States using predominantly technology-based methods. Technology is increasingly integrated into HIV research through sampling and recruitment methods via online advertisements on social media and dating apps as well as electronic peer referral methods [26,27]; electronic and remote data collection [28][29][30]; and remote specimen collection for biologic measures [31][32][33]. These tools have permitted enrollment of large samples of participants for behavioral surveys [34][35][36], cohort research [37][38][39], and intervention research [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…We also observed that peer-based interventions often incorporated personalized elements [ 34 , 38 , 55 , 56 ]. In a culturally-tailored counseling intervention, Black MSM interventionists helped participants identify and address their barriers to PrEP initiation (e.g., health insurance, mental health violence, alcohol and substance abuse) based on their prevention needs, and referred them to appropriate prevention resources [ 34 ].…”
Section: Resultsmentioning
confidence: 94%
“…Forty-two interventions were categorized into 5 socioecological levels and characteristics of interventions on each level are presented in Additional file 1 : Tables S1–S5, respectively. PrEP interventions for MSM were reported to implement in the US South (Florida, Georgia, Texas, Maryland, Mississippi, North Carolina and D.C.) [ 30 40 ], Northeast (Pennsylvania, New York, Massachusetts and Rhode Island) [ 27 , 31 33 , 36 , 38 , 41 49 ], Midwest (Illinois, Michigan, and Wisconsin) [ 24 26 , 32 , 33 , 36 , 47 , 50 – 52 ], West (California) [ 51 , 53 58 ] and nationwide [ 59 63 ]. Thirty-seven of the 42 studies focused solely on MSM [ 24 27 , 30 34 , 36 41 , 43 47 , 49 54 , 56 , 58 72 ], with some targeting Black, Hispanic/Latino MSM or MSM younger than 34 years old [ 24 27 , 30 34 , 36 40 , 44 46 , 49 , 50 , 52 , 56 , 58 , 60 63 , 70 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations